2018
DOI: 10.1159/000495845
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating DSM-5 and ICD-11 Diagnostic Features of Borderline Personality Disorder Using Schemas and Modes

Abstract: Background: Borderline personality disorder (BPD) comprises a heterogeneous constellation of problems operationalized in the DSM-5 and the forthcoming ICD-11. In schema therapy, schemas and modes are employed to conceptualize and treat these problems. Aim: The current study investigated whether the 9 diagnostic BPD features are associated with schemas and modes. Method: Psychiatric outpatients with predominant BPD features (n = 142; 68% females) were administered the Structured Clinical Interview for DSM-IV Ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
(48 reference statements)
0
7
0
1
Order By: Relevance
“…Perhaps unsurprisingly given the prevalence of NDP in BPD, schemas that include mistrust of others figure prominently in the disorder. These include distrust [25], mistrust/abuse [26,27], and disconnection/rejection [28]. The prevalence of mistrust/abuse beliefs may differentiate BPD from other personality disorders (e.g., [26,29]), and it has been suggested that the predominance of mistrustfulness/anger beliefs may define a subtype of BPD [30].…”
Section: Paranoia and Mistrust Beliefsmentioning
confidence: 99%
“…Perhaps unsurprisingly given the prevalence of NDP in BPD, schemas that include mistrust of others figure prominently in the disorder. These include distrust [25], mistrust/abuse [26,27], and disconnection/rejection [28]. The prevalence of mistrust/abuse beliefs may differentiate BPD from other personality disorders (e.g., [26,29]), and it has been suggested that the predominance of mistrustfulness/anger beliefs may define a subtype of BPD [30].…”
Section: Paranoia and Mistrust Beliefsmentioning
confidence: 99%
“…Several recent publications discuss the compatibility of the ST approach to PD conceptualization with recent developments in DSM-5-AMPD and ICD-11 PD (Bach & Lobbestael, 2018). In ST, the distinction between disorder and normal limits is determined by the frequency and intensity of schema activation and mode triggering, which is a dimensional approach.…”
Section: Concluding Remarks: St and The Transition To Dsm-5-ampd And ...mentioning
confidence: 99%
“…Zaključeno je da su grandioznost (makar skrivena/vulnerabilna) i traženje pažnje nužni za dijagnozu narcističnog poremećaja ličnosti, dok granični poremećaj ličnosti mora sadržavati barem jedan od sljedećeg -impulzivnost, rizično ponašanje i/ili hostilnost. Tako se trenutno najpreciznije očituje razlika između narcisa i borderline-a u formalnim dijagnostičkim kriterijima (51)(52)(53).…”
Section: From the Emptiness Of Borderline Personality Disorder To Social Hysteriaunclassified
“…It has been concluded that grandiosity (even hidden/vulnerable types) and attention-seeking are necessary for the diagnosis of narcissistic personality disorder, whereas borderline personality disorder much include at least one of the following -impulsivity, risky behavior, and/or hostility. This is currently the most precise way to describe the difference between narcissistic and borderline personality disorder in formal diagnostic criteria (51)(52)(53).…”
Section: From the Emptiness Of Borderline Personality Disorder To Social Hysteriamentioning
confidence: 99%